Bilateral axillary lymph node metastasis after radioactive ablation in recurrent papillary thyroid carcinoma: A case report - Rahmat, Beatta Meidini; Irawati, Nina (Edelweiss Applied Science and Technology, 2025)
Papillary thyroid carcinoma (PTC) is associated with indolent growth and a good prognosis. PTC has a tendency to metastasize into nearby lymph nodes, and 10% of PTC cases may present with metastatic disease. Axillary lymph node metastasis (ALNM) is an ineffably scarce event in thyroid carcinoma, and it may indicate a poor prognosis, with only a few cases reported in the literature. A 44-year-old woman with a previous history of total thyroidectomy, left radical neck dissection, and radioactive iodine (RAI) ablation was clinically presented with a recurrent thyroid mass, cervical lymphadenopathy, extensive skin involvement, and bilateral axillary lymph nodes from metastatic papillary thyroid carcinoma. Imaging scans revealed metastasis to the lungs and cervical bone. She was managed by completion total thyroidectomy, wide excision for the suprasternal nodules, completion left neck dissection, type 3 modified radical right neck dissection, bilateral central compartment clearance, and standard bilateral axillary dissection. ALNM is associated with aggressive histopathology, extensive locoregional disease, and distant metastasis. ALNM in thyroid cancer is uncommon since there is no direct connection between the neck and axilla; thus, ALNM is a culmination of an uncommon pattern. Risk factors contributing to ALNM include skin involvement, bulky cervical lymph nodes, previous surgery, and radiation. Complete surgical resection is the main therapy to achieve the effectiveness of adjuvant therapy.